Arahan Zonasi Minapolitan Dalam Meningkatkan Perekonomian Kota Pesisir - Regita Chahyani Abdul Gani; Slamet Trisutomo; Sri Aliah Ekawati (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2020)
Palopo is a coastal city that has experienced excessive exploitation of fishery resources and decreased income from the fisheries sector. This condition does not support the realization of the minapolitan vision as stipulated in the Palopo City Spatial Planning (RTRW). This study aims to determine the potential and problems related to fishery resources, human resources, facilities, infrastructure and the level of vulnerability to natural disasters, as well as to recommend minapolitan zoning directions in the coastal area of ​​Palopo City in improving the regional economy. The method used is descriptive qualitative analysis, Location Quotient (LQ), employment, Likert scale and spatial. This research took place from October 2019-March 2020. This research is located in Palopo City. The results showed that fishery resources in Palopo City experienced a decline in production due to an increase in population. Of the five coastal districts, three of them have a capture fishery base and two are aquaculture, but the highest fishery production currently is the aquaculture sub-sector. The aspect of human resources shows that 70% of the total population of each sub-district is a ready-to-work population with the largest number of fishermen in the East Wara District. The facilities and infrastructure in this city have a sufficient level of availability of fishery facilities at this time. The location that has a low level of natural disaster vulnerability is Wara Timur District. In improving the fishery sector in this city, zoning in the coastal area is divided into three parts, namely the core, support and marketing zones.